Effect of Mediterranean Diet Enriched in High Quality Extra Virgin Olive Oil on Oxidative Stress, Inflammation and Gut Microbiota in Obese and Normal Weight Adult Subjects - Luisi, Maria Luisa Eliana; Lucarini, Laura; Biffi, Barbara; Rafanelli, Elena; Pietramellara, Giacomo; Durante, Mariaconcetta; Vidali, Sofia; Provensi, Gustavo; Madiai, Sara; Gheri, Chiara Francesca; Masini, Emanuela; Ceccherini, Maria Teresa (Frontiers in Pharmacology, 2019)
Introduction: The Mediterranean Diet (MD) is useful in the prevention of overweight, obesity and metabolic disease. High Quality-Extra Virgin Olive Oil (HQ-EVOO), an essential component of this diet, exerts protective effects against chronic diseases. Gut Microbiota (GM), recognized as a key factor in driving metabolic activities, is involved in the regulation of host immunity. Lactic Acid Bacteria (LAB) and their probio-active cellular substances produce beneficial effects in the gastrointestinal tract. Materials and Methods: Eighteen overweight/obese subjects (cases, BMI ≥25 kg/m2) and 18 normal weight controls (BMI 18.5–24.9 kg/m2) were fed with MD enriched with 40 g/die HQ-EVOO for three months. Feces and blood samples were collected at time 0 (T0) and after three months (T1) for LAB composition, oxidative stress, metabolic and inflammation parameter determinations. Results: Myeloperoxidase and 8-hydroxy-2-deoxyguanosine, markers of inflammation and oxidative stress, were significantly decreased after MD rich in HQ-EVOO both in controls and in cases. Proinflammatory cytokines levels were significantly decreased in cases in comparison to controls, while IL-10 and adiponectin were significantly increased in cases. LAB’s rpoB copies/ng of DNA increased 55.6 folds in cases compared to their baseline after MD rich in HQ-EVOO. MD rich in HQ-EVOO increased adiponectin and IL-10 concentration in overweight/obese subjects and decreased oxidative stress and inflammation parameters and at the same time, increased LAB number in GM. Discussion: Our results indicate that MD rich in HQ-EVOO induces an increase of LAB in GM and could have a potential role in the prevention of inflammation. Clinical Trial Registration:www.ClinicalTrials.gov, identifier NCT03441802.